2018
DOI: 10.1002/jbm.a.36572
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of survival and migration potential of differentiated cardiomyocytes transplanted with decellularized heart scaffold

Abstract: Mesenchymal stem cell‐derived cardiomyocytes are employed as a source for myocardial cell transplantation as well as for tissue engineering in decellularized tissue scaffolds. The present study aimed at investigating the survival and migration potential of differentiated cardiomyocytes integrated to decellularized scaffolds after implantation into retroperitoneum of rats, and to assess the feasibility of their ectopic use for future cardiovascular tissue engineering. For this purpose, adipose tissue‐derived me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…To successfully apply hPDLSCs to stem cell therapy, it is crucial to monitor and track the transplanted cells in vivo and distinguish whether cellular regeneration is originated from the exogenous cell source. [ 16,17 ] To achieve this, cell labeling agents are commonly used, such as bromodeoxyuridine (BrdU), [ 18 ] superparamagnetic iron oxide nanoparticles (SPIONs), [ 19 ] and fluorescent agents [ 20,21 ] like green fluorescent protein (GFP). [ 22 ] However, BrdU is dependent on immunohistochemical (IHC) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To successfully apply hPDLSCs to stem cell therapy, it is crucial to monitor and track the transplanted cells in vivo and distinguish whether cellular regeneration is originated from the exogenous cell source. [ 16,17 ] To achieve this, cell labeling agents are commonly used, such as bromodeoxyuridine (BrdU), [ 18 ] superparamagnetic iron oxide nanoparticles (SPIONs), [ 19 ] and fluorescent agents [ 20,21 ] like green fluorescent protein (GFP). [ 22 ] However, BrdU is dependent on immunohistochemical (IHC) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, biomaterials technology combined with cellular therapy plays a huge role in cardiovascular diseases ( 165 , 166 ). For example, treatments with collagen can promote cardiomyogenic differentiation of MSCs ( 167 , 168 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study transplanting labeled cell-loaded testis scaffolds showed appropriate cell migration to the recipient tissue, indicating that a testicular ECM scaffold could be a promising vehicle to support cell transplantation [ 102 ]. A decellularized heart tissue scaffold was also reported to successfully deliver exogenous cardiomyocytes to the retroperitoneum of recipient animals [ 103 ].…”
Section: Applications Of Ecm Scaffolds From Other Sources In Tissue E...mentioning
confidence: 99%